1979
DOI: 10.1161/01.res.45.2.275
|View full text |Cite
|
Sign up to set email alerts
|

Specific antibody to hog renal renin and its application to the direct radioimmunoassay of renin in various organs.

Abstract: SUMMARY We produced anti-hog renin antibodies using as antigens pure hog renal renin that either had been insolubilized or conjugated to tetanus toxoid. High titer antibodies were obtained, which demonstrated different cross-reactivity with renins from other species. A direct radioimmunoassay for renin was developed using antibody, monoiodinated lu I-hog renin, and various methods for separating free and antibody-bound trace. This assay was capable of detecting 40 pg of hog renin and was applied to the determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
1

Year Published

1981
1981
1992
1992

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…The renin, with a specific activity of 346 GU per mg protein, was polymerized with glutaraldehyde. 9 BALB/c mice received an initial subcutaneous dose of 360 fig of renin preparation with Freund's complete adjuvant. After 53 days, the mice received a second subcutaneous dose of 180 /xg renin with Freund's incomplete adjuvant.…”
Section: Immunization Of Micementioning
confidence: 99%
“…The renin, with a specific activity of 346 GU per mg protein, was polymerized with glutaraldehyde. 9 BALB/c mice received an initial subcutaneous dose of 360 fig of renin preparation with Freund's complete adjuvant. After 53 days, the mice received a second subcutaneous dose of 180 /xg renin with Freund's incomplete adjuvant.…”
Section: Immunization Of Micementioning
confidence: 99%
“…The proportion of renin-like activity that was inhibited by the antirenin antibody was determined by preincubating the extract with the antiserum (1:100) or with preimmune serum (1:100) for 24 hours at 4° C prior to the AI generation reaction described above. Antisera to hog, 10 rat,…”
Section: Antiserummentioning
confidence: 99%
“…Talwar et al 67 reported that when a human protein is conjugated to tetanus toxoid, the protein gains antigenicity in humans, and applied it for raising autoantibodies against human chorionic gonadotrophin in men as a means for male contraception. We conjugated hog 68 and rat renin 69 to tetanus toxoid and were able to raise high affinity antibodies suitable for its immunohistochemical localization. Later renin-bovine thyroglobulin conjugates were found to be appropriate as a strong immunogen.…”
mentioning
confidence: 99%
“…95 and vascular tissues. 96 The antibodies permitted direct immunoassay of hog 68 and rat 69 renin. However, the thresholds of detection were 40 pg/ml for hog renin and 100 pg/ml for rat renin, which were an order of magnitude less sensitive compared with renin activity assay.…”
mentioning
confidence: 99%